Interpretasi Ma’nā Cum Maghzā Terhadap Relasi Suami-Istri dalam QS. al-Mujādalah [58]: 1-4. (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
Husband and wife relationship is an issue that is always fun to discuss. Many classical literary traditions that leave behind patriarchal culture, therefore this article discusses the question of marital relations in the Qur'an. For example, the wife is often positioned as a person who gets rough, unfair, and discriminatory treatment, even if examined in the QS. Mujādalah [58]: 1-4 shows how God is very concerned about women who are not treated well by their husbands. Through the theory of ma'nā cum maghzā which was popularized by Sahiron Syamsuddin, the writer wanted to offer a new discourse on modern interpretation which covered three things. First interpretation system, linguistic analysis. Second, historical analysis includes asbāb al-nuzūl macro and micro, intratextextuality (munāsabah al-āyat) and itertextextats (isra'iliyyat), Third, namely significance, searching for the deepest meaning of ma'nā towards maghzā of conjugal relations.